PRIVACY- AND INTEGRITY-PRESERVING ENTIRE RANGE QUERIES IN SENSOR NETWORKS - Pradip Krishnadeo Patil; Nilesh Ashokrao Thorat (International Journal of Innovations in Engineering Research and Technology, 2021)
The architecture of two-tiered sensor networks, where storage nodes serve as an intermediate tier between sensors and a sink for storing data and processing queries has been widely adopted because of the benefits of power and storage saving for sensors as well as the efficiency of query processing. However, the importance of storage nodes also makes them attractive to attackers. This paper we proposed Paillier Cryptosystem that prevents attackers from gaining information from both sensor collected data and sink issued queries. To preserve Privacy, A paillier cryptosystem is a modular, public key encryption scheme, using this scheme both data and query message are encrypted such that storage node can correctly decrypt messages of an encrypted query over encrypted data without knowing their value in the message. To preserve integrity, we propose two schemes—one using Merkle hash trees and another using a new data structure called neighborhood chains—to generate integrity verification information so that a sink can use this information to verify whether the result of a query contains exactly the data items that satisfy the query.